Health Belief Model in Quranic Perspective: A Synthesizing themes of Health Behavior - Chandra Kartika Dewi; Moch. Ali Mutawakkil (Islamic Religious Education Departement, 2023)
The encouragement of worship described by the Qur'an in various verses has another dimension related to the health belief model construction. This study aims to identify the formation of beliefs in actions that lead a person to healthy behaviours depicted in various verses by nahyu (prohibition) and amr (command). This study uses qualitative methods with a thematic analysis model to achieve this goal. A search of the various verses shows a pattern of the Qur'an's awareness of changes in actions correlated with statements about the potential risks that threaten humans that may prevent them from worshipping. Fear of the threat of danger as a driving mechanism for change in action is strengthened by motivating the benefits obtained in acting. The two aspects of consciousness, risk, and profit are driven by self-confidence that arises from awareness of servitude. The embodiment of the health beliefs model in the Qur'an represents the divine dimension that manifests in fulfilling the obligation to produce healthy behaviours.